Vers la protection du patrimoine postmoderne - Bastien Couturier (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Modern architectural heritage, as well as the various styles that preceded it, enjoys great international acknowledgement and many heritage protection measures from European national institutions. Post-modern heritage, however, seems to be largely ignored from the lists of historical monuments. The aim of this study is to compare postmodern buildings recognised and protected in France, Italy, Spain and the United Kingdom. We will analyse current legislation to understand the regulatory obstacles to the acknowledgement of architectural heritage and the protection of post-modern buildings.